The process of creating short film works using hybrid animation techniques - Rosita, Ely (Jurnal Desain, 2025)
The animated short film Finding a Dream highlights the artist's emotional relationship with his father through dream symbolism, using hybrid animation techniques that combine 2D and 3D elements to create a dynamic and aesthetic visual narrative. The creation process is carried out through three main stages: pre-production, production, and post-production. In the pre-production stage, story ideas are explored based on personal experiences, followed by creating storyboards and character designs. The production stage includes experiments combining 2D and 3D animation elements through key-posing, in between, modeling, and rendering techniques. Post-production involves refining visual and audio elements to ensure a cohesive narrative. As a result, this film successfully combines visual and audio elements harmoniously, showing aesthetic interactions between 2D characters and 3D environments. The hybrid animation technique provides creative flexibility in expressing complex symbolism while creating relevant visual innovation amidst the competitive global animation industry. Apart from being a personal expression of the creator, this work is also an important contribution to the development of hybrid animation in Indonesia, offering an inspiring creative alternative for further exploration in the future.